Case Report: A neurolinguistic and neuroimaging study on a Chinese follow-up case with logopenic-variant of primary progressive aphasia - Huang, Binyao; Wang, Xiaolu; Jiang, Biao; Kong, Linlin; Hou, Haifeng; Zhou, Jiong (Frontiers in Neurology, 2022)
Primary progressive aphasia (PPA), typically resulting from a neurodegenerative disease, is characterized by a progressive loss of specific language functions while other cognitive domains are relatively unaffected. The logopenic variant, characterized by impairments of word retrieval and sentence repetition along with preserved semantic, syntactic, and motor speech abilities, is the most recently described and remains less understood than other variants due to a comparatively small number of case studies and a lack of investigations with a thorough specification. In this article, we report a 2-year follow-up case study of a 74-year-old Chinese female patient with a logopenic variant of primary progressive aphasia, including its neurolinguistic study, magnetic resonance imaging (MRI), and 11C-Pittsburgh compound B-Positron emission tomography imaging analyses, as well as gene sequencing. This case confirms that, in addition to word-finding and sentence repetition difficulties, the logopenic variant may also present with mild auditory comprehension and naming deficits attributed to impaired access to lexical representations. The observation of clinical treatment suggests the efficacy of memantine hydrochloride tablet and rivastigmine transdermal patch in slowing down the cognitive deterioration of this patient. The description and exploration of this case may shed new insights into a better understanding of the Chinese logopenic variant of primary progressive aphasia.